Household crowding is associated with higher allostatic load among the Inuit. Issue 4 (2nd January 2014) - Riva, Mylene; Plusquellec, Pierrich; Juster, Robert-Paul; Laouan-Sidi, Elhadji A; Abdous, Belkacem; Lucas, Michel; Dery, Serge; Dewailly, Eric
Abstract : Background: Household crowding is an important problem in some aboriginal communities that is reaching particularly high levels among the circumpolar Inuit. Living in overcrowded conditions may endanger health via stress pathophysiology. This study examines whether higher household crowding is associated with stress-related physiological dysregulations among the Inuit. Methods: Cross-sectional data on 822 Inuit adults were taken from the 2004 Qanuippitaa? How are we? Nunavik Inuit Health Survey. Chronic stress was measured using the concept of allostatic load (AL) representing the multisystemic biological 'wear and tear' of chronic stress. A summary index of AL was constructed using 14 physiological indicators compiled into a traditional count-based index and a binary variable that contrasted people at risk on at least seven physiological indicators. Household crowding was measured using indicators of household size (total number of people and number of children per house) and overcrowding defined as more than one person per room. Data were analysed using weighted Generalised Estimating Equations controlling for participants' age, sex, income, diet and involvement in traditional activities. Results: Higher household crowding was significantly associated with elevated AL levels and with greater odds of being at risk on at least seven physiological indicators, especially among women and independently of individuals' characteristics. Conclusions: This study demonstrates that household crowding is a source of chronic stress among the Inuit of Nunavik. Differential housing conditions are shown to be a marker of health inequalities among this population. Housing conditions are a critical public health issue in many aboriginal communities that must be investigated further to inform healthy and sustainable housing strategies.